Buffalo (Bubalus bubali) Late Embryo and Foetus Development: A Morphological Analysis - Morini, A. C.; Pieri, N. C. G.; Roballo, K. C. S.; Martins, D. S.; Ambrosio, C. E.; Morini Junior, J. C.; Favaron, P. O.; Minervino, A. H. H.; Pereira, F. V. T. [UNESP]; Miglino, M. A. (Wiley-Blackwell, 2016)
Contents Many researches describe the embryonic developmental features in domestic animals; however, in farm animals, they are scarce. Most farm animal studies are related to assisted reproduction and embryos transfer techniques. But, morphological features and size measure to estimate the age gestation are rarely reported in literature. Thus, in this study, we described the developmental changes in the bubaline (Bubalus bubali) concepts from 21 to 60days of gestation. Our results revealed that buffalo embryos similar morphological characteristics similar to other mammalian species. Also, similarities between bovine and bubaline persist; except on foetal stages when buffalos have a faster development than bovine. Therefore, buffalo's gestation period exhibits some varieties and accurate embryo age is more difficult. Yet, when we use a combination of the crown-rump, macroscopic analysis and alizarin red, it is possible to describe better the whole embryogenesis stages of the buffalo and which can contribute for future reproduction researches and applications in veterinary practice.